Extreme (and non-extreme) punishments in sender-receiver games with judicial error: An experimental investigation - Fong, Meng-Jhang; Wang, Joseph Tao-yi (Frontiers in Behavioral Economics, 2023)
We conduct an experiment which incorporates ex post punishment and judicial uncertainty into the discrete sender-receiver game of Crawford and Sobel (1982), where a knowledgeable sender sends a cheap-talk message to a receiver who determines a policy action. After taking this action, the receiver observes a noisy signal of the true state and can impose a costly punishment on the sender. We vary the strength of punishment from mild (nominal), strong (deterrent) to extreme (potential of losing everything), and vary receiver’s signal uncertainty when punishment is extreme. We find that receivers punish less as the strength of punishment increases, which suggests a trade-off between wrongly punishing innocent senders and not being able to punish liars. More importantly, punishment encourages receivers to trust senders more and thus improves the information transmission, even though senders need not become more truthful.